2009
DOI: 10.21859/isv.3.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of HGV RNA in Chronic Hepatitis Patients from Afzalipoor General Hospital in Kerman, Iran

Abstract: Background and Aims: Viral hepatitis is a global health problem with a high mortality rate. Recently, a new Flavi-like virus, provisionally named hepatitis G virus (HGV), has been described. HGV does not induce an immune response that is consistently detectable by using recombinant proteins from prokaryotic expression, therefore studies have been conducted by using polymerase chain reaction (PCR) based system. HGV is a blood born virus that is parenterally transmitted, however incidence of severe hepatitis wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Another study in Iran reported that HGV co-infection was highly prevalent among Korean blood donors who are infected with HBV or HCV. The same study revealed that population negative for HCV and HBV are a low risk group for HGV infection (15). Frequency of anti-E2 of HGV in βthalassemia major patients was reported to be 25% (16).…”
Section: Resultsmentioning
confidence: 90%
“…Another study in Iran reported that HGV co-infection was highly prevalent among Korean blood donors who are infected with HBV or HCV. The same study revealed that population negative for HCV and HBV are a low risk group for HGV infection (15). Frequency of anti-E2 of HGV in βthalassemia major patients was reported to be 25% (16).…”
Section: Resultsmentioning
confidence: 90%
“…In addition, Zahedi et al found that half of those with positive marker of HGV infection (HGV RNA) were cirrhotic, whereas only 9.5% of those without positive marker of HGV infection were cirrhotic ( 10 ). Moreover, molecular evaluation of HGV and HCV in patients with chronic renal failure in Iran detected HGV-RNA in 17.74% of the patients and in 3% of blood donors ( 11 ).…”
Section: Introductionmentioning
confidence: 99%